Heparin and commercial bothropic antivenom against the paralyzing effect of Bothrops jararacussu snake venom - S Rostelato-Ferreira (Journal of Venomous Animals and Toxins including Tropical Diseases, 2010)
The crude venom of Bothrops jararacussu (Bjssu) is known to induce muscular paralysis in vitro. Many studies have shown that various substances, including heparin, neutralize the damage caused by snake venom. In the present study, the ability of heparin (Hep) and commercial bothropic antivenom (CBA) to neutralize neuromuscular effects of Bjssu venom, at different time-points, was analyzed. Mouse phrenic nerve-diaphragm preparation was used through a conventional myographic technique, following five different protocols: Group 1 was incubated with Bjssu (40 µg/mL) without any other treatment; Groups 2 and 3 were pretreated with heparin (1 µL/mL) and CBA (120 µL/mL), respectively, for 15 minutes before venom addition; Group 4 after 50% neuromuscular blockade induced by Bjssu crude venom received 1 µL/mL of heparin while Group 5 received a mixture of Hep:CBA:Bjssu. Control preparations (Tyrode) were treated with Hep and CBA (mean ± SEM; n = 3-6). After 120 minutes of venom incubation, Group 1 preparations presented twitch-tension of 12 ± 2%. However, in Groups 2 and 3, the neutralizations were 92 ± 1.9% and 81 ± 6%, respectively. The heparin addition, after 50% neuromuscular blockade by Bjssu, produced 40 ± 6% muscular response after 120 minutes of incubation. Hep:CBA:Bjssu mixture displayed a protective effect of 84 ± 10% against venom action. In conclusion, heparin and commercial bothropic antivenom efficiently neutralized the neurotoxic effects caused by B. jararacussu crude venom, even at different incubation time-points.